Comparison of fit factors among healthcare providers working in the Emergency Department Center before and after training with three types of N95 and higher filter respirators - Kim, Hongjung (Medicine (Baltimore), 2019)
INTRODUCTION: N95 or higher filtering respirators have been recommended in healthcare settings, although there is still a risk of infection due to the improper selection and wearing of respirators. We aimed to assess the effects of training with N95 or higher filter respirators on the protection performance of respirators among healthcare providers in the emergency medical center (EMC). METHODS: This randomized crossover study evaluated 23 healthcare providers. Quantitative fit tests (QNFTs) were performed before and after training using three types of N95 or higher filter respirators (cup-type, fold-type, valve-type). Training was performed by lecture, real-time feedback, and fit check. The primary outcome was the fit factor, and the secondary outcomes were overall fit factor, adequate protection rate, and respiratory preference. RESULTS: Fit factors, overall fit factor, and adequate protection rate were higher after training than before training for the 3 types of respirators (all P < .05). For normal breathing, fit factors before and after training were 121 (10–185) vs 192 (161–200) for cup-type, 200 (39–200) vs 200 (200–200) for fold-type, and 85 (18–157) vs 173 (117–200) for valve-type. For normal breathing, the adequate protection rates before and after training were 62 (0–100) vs 100 (90–100) for cup-type, 100 (0–100) vs 100 (100–100) for fold-type, and 19 (0–100) vs 100 (44–100) for valve-type (all P < .05). The most preferred respirator type was the valve-type (10 persons, 45.5%). CONCLUSIONS: Training on wearing an N95 or higher respirator improved the protection performance of respirators among healthcare providers working in the EMC. The selection of proper respirators and training would be beneficial to the safety of healthcare providers.